PENGARUH GAYA HIDUP TERHADAP KESEHATAN PASIEN HIPERTENSI DAN DIABETES MELITUS KLINIK MAKMUR JAYA, TANGERANG SELATAN - Ayat Rahayu; Fajr Muzzammil; Sakinah Mawaddah Ramadhaniah; Nurul Fathia Shafira Amiyanti; Abdul Rahman; Komalasari Komalasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Hypertension and diabetes mellitus (DM) can cause various serious complications, even death. One factor that determines the health condition of patients with hypertension and DM is lifestyle. Unhealthy lifestyle habits, such as an inappropriate diet, lack of physical activity, and smoking habits, are the main triggers for the emergence of hypertension and DM. This study used a cross-sectional study design with the PLS-SEM analysis method. Primary data with a sample of 80 patients with hypertension and DM. The research findings revealed that lifestyle has a positive and significant influence on the health of patients with hypertension and DM. The most dominant indicator in the lifestyle variable was routine check-ups (0.943 > 0.70 (loading factor)), while the main indicator in the patient health variable was uric acid levels with a loading factor value of 0.830. The Composite Reliability value for lifestyle variables (0.856) and patient health (0.861) > 0.7, indicating a reliable instrument, and the Average Variance Extracted value of 0.750 and 0.675 > 0.50, respectively, indicating that convergent validity is met. The results show that lifestyle has a positive and significant effect on the health of hypertension and DM patients (t-statistic = 11.951 > 1.96; p-value = 0.000 < 0.05; original sample = 0.774).